Vivências tecnológicas da rede SESI-SP : uma estratégia organizacional para auxiliar o processo de ensino e aprendizagem - Lucas, Giseli de Souza (Universidade Federal de São Carlos, 2015)
The aim of this work is to discuss whether the lessons of Technological Experience, taught students of elementary school, the network of Industry Social Service SESI São Paulo / SP, is a pedagogical strategy that helps students in school literacy and digital autonomy . It is noticeable trend of increasingly frequent use of computers and other technology in school education, therefore, Technological Experience has been deployed in the network to enhance the teaching and methodological aspects of teaching and learning. Therefore, this research aims to analyze the dynamics of this moment of "Technology Experience," which received the grant from the constructivist theory, and whether the classes in the Computer Lab and assemblies and programs in Science and Technology Laboratory, with the blocks assembly, contributing to the achievement of teaching methodologies related to the development of thinking, reasoning, problem solving, the reading and writing practices. We will use mainly as a theoretical framework, related to Information and Communication Technologies (ICT), the authors: Belloni (2009), Kenski (0000), Levy (1993), Papert (2008), Valente (1998) that address the interaction technology with society. To the field of literacy and literacy, we will use the Blacksmith's research (2001), Kleiman (1995), Miller (2010) and Smith (2007). We opted for the research methodology, Case Study for the development of objectives, which adopted the semi-structured interviews, participant observation and document analysis (LUDKE; ANDRÉ, 2012), involving two teachers from SESI network / SP, a the first year of elementary school and one of the room "Technological Vivencia" it is formed of educational computing area, working as an IT support analyst. The research sought to understand the relationship between the two professionals, identifying the link between the educational material, computer classes and regular classes in the classroom the first year. This work enabled the deepening of characteristics, evaluating the quality of the relationship and socialization between these two spheres training for the student's first year of elementary school, identifying the methodological procedures and also investigate the professionalization of educational agents and their training.
Keywords: Vivência tecnologia; Autonomia digital; Metodologia de ensino; Experience technology; Digital autonomy; Teaching methodologies; CIENCIAS HUMANAS::EDUCACAO